MODERN APPROACHES TO COMPETITIVE DEVELOPMENT OF UNIVERSITIES - Zayarnaya, *Irina Aleksandrovna (Nuances: estudos sobre Educação, 2019)
The purpose of the studyis to present theory and methods of efficient system of university’s competitiveness development. Design/Methodology/Approach The methods of study included chronological method, system analysis of statistical information, expert evaluation method, and mathematical data processing. Findings Creation of an innovative university requires a qualitative change of technology and the content of educational, scientific, methodical, economic and industrial activities of the university. To achieve long-term success in asserting the university on educational market, the work should be performed in all the spheres and by all the aspects of its activities. It is very important to take into account specifics of interrelation between a higher education establishment and external environment; the university managers should objectively evaluate the university’s position in the market of educational services, understand the necessity of changes, and predict the effects of introduced amendments. There are different strategies aimed to achieve high competitiveness of a university including internalization of higher education and creation of entrepreneurial universities. Originality/Value The results represented in the article can be used by the heads of higher education establishments to optimize the system of universities’ competitiveness management. The article may also be useful for specialists who prepare study editions and guides for students specializing in management in education, and non-specialists interested in this topic.